Akuntabilitas Publik Dari Aspek Pembukuan, Inventarisasi, dan Pelaporan Aset Tetap - Sukmini Hartati; Choiruddin .; Hadi Winarko; Rita Martini (Politeknik Negeri Sriwijaya, 2020)
This study aims to analyze the effect of the administration of fixed assets on public accountability. The sample used was 30 OPD in Palembang. The analytical technic used is multiple regression analysis. The novelty of this research, the administration of fixed assets analyzed refers to Permendagri Number 19 of 2016, covering the dimensions of bookkeeping, inventory and reporting. Public accountability is seen from the accountability of policies, programs, processes, as well as honesty and law. The results showed partially that the inventory and reporting variables had a positive and significant influence while bookkeeping did not have a positive and significant influence on the public accountability, and simultaneously had significant effect.